Determination of forest fire causes in Portugal (1966-2010) - Lourenço, Luciano (2013)
The main goal of this study is to analyse the most important causes affecting fire ignitions in Portugal mainland, between 1996 and 2010. The forest fire database was provided by the Portuguese Government Forest Services (National Forest Authority, AFN), that group the causes in six main categories (negligent usage of fire, accidental, structural causes, incendiary, natural and unknown). The analysis of the causes of the forest fires ignitions shows that the greatest part was not investigated (84%), whilst the knowledge of cause only occurred in 8% of fires. At national level, the results show that incendiary and the negligent usage of the fire are the most important motivations behind forest fires, with almost 40% of the identified causes. At regional scale, fires caused by negligence seems to be more common in the north due to traditional agricultural practices such as pasture renewal, the burning of agricultural and forest debris and hunting practices. In the Alentejo, accidental causes mainly associated with crop harvesting machinery, were the primary reason for the outbreak of forest fires.